External laryngocele in an adult: a case report - Tamilchelvan, Surintheren Kumar; Rozhan, 'Atikah; Kuppusamy, Sharmini; Hamid, Zubaidah (2024)
Laryngocele is a rare condition marked by an abnormal enlargement of the air-filled saccule of the laryngeal ventricle. This case report showcases a distinctive presentation of external laryngocele to assist clinicians in its diagnosis and management. A 43-year-old male, with a 20-year history of painless swelling on the right side of his neck, likened to the size of an orange, presented with a recent increment in size. He noticed a gurgling sound when pressing on the swelling but did not experience any hoarseness or difficulty swallowing. During the physical examination, it was observed that there was a swelling on the right side of the neck at level II that measured approximately 3 x 5 cm. This swelling seemed to increase when the Valsalva maneuver was performed. A computed tomography scan revealed a 5 x 3 cm air-filled lesion, indicative of an external laryngocele. Although surgical excision was advised, the patient decided not to proceed with treatment and did not attend follow-up appointments. Laryngocele mainly impacts men, especially those in their fifth and sixth decades of life and is linked to activities that raise laryngeal pressure. Diagnosis is mainly based on clinical evaluation, complemented by imaging techniques such as CT and MRI. Surgical excision remains the preferred treatment, with approaches differing, depending on the laryngocele subtype. This particular case highlights the infrequency of laryngocele, and how it may manifest as a swelling in the neck. It underscores the importance of clinicians being aware of this harmless condition, highlighting the significance of taking a detailed patient history and using suitable imaging for accurate diagnosis and effective management, especially to rule out any malignancies. This report adds to the current body of knowledge on laryngocele, offering valuable information on its clinical symptoms and treatment implications.